Chemicals - up close. Plastic shoes from all over the world (Stockholm, 2010)
"The shoe industry is one of the most globalised industries in the world. Shoes, and in particular plastic shoes that have been analysed in this study, have become a throwaway item for many people the world over. Many different types of chemical that can cause health and environmental problems are used in the manufacture of plastic shoes. These chemicals can cause harm to the workers who handle the chemicals or the shoes. They can harm the environment as the shoes wear out and when they are discarded. The chemicals can also cause health problems for the people who wear the shoes. However, a person who buys a pair of shoes seldom knows which chemicals they contain or where the shoes were made."